Characterization and application of synthesized calcium alginate-graphene oxide for the removal of Cr3+, Cu2+ and Cd2+ ions from tannery effluents - Sobur Ahmed; Tasrina Rabia Choudhury; Md. Zahangir Alam; Mohammad Nurnabi (Cleaner Water)
Environmental sustainability has gained acceptance to achieving the goal of a secure ecosystem with a reliable management system. Heavy metal remediation of aqueous streams is of special concern due to the intractability and persistence in the environment. Adsorption is a potential alternative to the existing inefficient conventional technologies for the removal and recovery of metal ions from aqueous solutions and becomes vital to align with the Sustainable Development Goals (SDGs) and mitigate the adverse environmental and social impacts. Calcium Alginate-Graphene oxide (CA-GO) composite has been synthesized for the adsorption of heavy metals including Cr3+, Cu2+, and Cd2+ ions from tannery effluents. Graphene oxide is prepared from commercial graphite powder and reacted with sodium alginate and calcium chloride to form the beads of CA-GO composite. The developed composite was characterized by FTIR, elemental analysis, SEM, XRD analysis, and Raman spectroscopy. Moreover, the effect of pH, adsorbent dosage, contact time, and initial concentration of metal ions on the adsorption capacity were investigated through batch experiments. At a pH>3.0 (pHzpc), the carboxyl group of CA-GO was deprotonated to make the surface negatively charged and facilitate metal adsorption. The optimum pH and maximum adsorption capacity of CA-GO for removal of Cr(III), Cu(II), and Cd(II) were 4.5, 6.0, and 7.0, and 90.58, 108.57, and 134.77 mg g−1, respectively. The kinetics, adsorption isotherms, and thermodynamics were studied to determine the adsorption mechanism. The kinetic of adsorption adopted the second-order model. Thermodynamic parameter were calculated and the adsorption process was determined to be exothermic and spontaneous at room temperature. The developed composite has been efficaciously applied for the removal of metal ions and pollution from real tannery effluents.